Language as a Fundamental Source for National Integration: The Case of Pakistan (Journal of Asian Development Studies, 2023)
National integration has become a main clause and challenge for the post-colonial developed societies of Asia and Africa. Many strategies were adopted to grow national integration, but solutions remained complex. In Pakistan, a third-world plural society that is a multi-ethnic and multilingual state, national integration faces constant challenges. Pakistan has consistently used centralizing and oppressive policies to establish national integration as a federal state. The state's authoritative policies turned ethnic and language riots into politics. This paper mainly enumerates the role of the Urdu language as a primary source for nationalism and national integration. In the past, the separation of East Pakistan in 1971 was the outcome of language riots. Recently, the National Language (Urdu) became a fundamental source for national integration to establish regional harmony and communication among provinces and different ethnic groups of Pakistan. Urdu serves as a tool for national integration, as it is an amalgamation of multiple languages from the past and present.